2003
DOI: 10.7863/jum.2003.22.9.945
|View full text |Cite
|
Sign up to set email alerts
|

Acute Appendicitis Mimicking Infectious Enteritis

Abstract: Objective. To verify the role of sonography in screening of acute appendicitis in patients admitted to an infectious disease unit for suspected acute infectious enteritis. Methods. One hundred eighty consecutive patients (102 male and 78 female; age range, 5-72 years; mean age, 31 years) admitted for suspected infectious enteritis or typhoid fever were prospectively studied with abdominal sonography within 48 hours after admission. None of the patients had peritoneal irritation. Forty-six patients (25%) had wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The normal appendix can be visualized in approximately 12-82% of patients [16,[18][19][20][21]. In inflamed appendices, this rate increases to up to 95% [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal appendix can be visualized in approximately 12-82% of patients [16,[18][19][20][21]. In inflamed appendices, this rate increases to up to 95% [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, even to experienced sonographers, the normal vermiform appendix is not always visible sonographically. With conventional US imaging, a normal appendix can be clearly identified in 12-82% of cases [16,[18][19][20][21]. This rate is higher in pathologic appendices [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely shown that ultrasound may reveal a high incidence of infectious ileocecitis in patients with acute right lower quadrant pain where appendicitis is suspected (Puylaert et al 1988(Puylaert et al , 1997Tarantino et al 2003). Sonography may also reveal the features of the bowel wall useful in the differential diagnosis between infectious ileocolitis, Crohn's disease and appendicitis (Table 1).…”
Section: Infectious Ileocecitismentioning
confidence: 99%
“…Therefore, in individuals presenting with abdominal pain, diarrhoea and fever, or patients with acute or atypical symptoms and infants, as well as immunocompromised and elderly patients where a differential diagnosis between bacterial infectious enteritis and other acute abdominal conditions is mandatory, ultrasound can be employed to avoid unnecessary laparotomies and to avoid delay of surgery or specific therapy ( Fig. 1) (Puylaert 1994;Tarantino et al 2003).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…However, the symptoms of AA (fever and right lower abdominal pain) are often similar to those observed in acute infectious enteritis (AIE). [1][2][3] Early diagnosis can be difficult in cases in which the sonographic appearance of AA is not typical. Therefore, the present study assessed the ability of sonography to visualize the normal appendix in AIE compared with a control group of normal appendices and a group of patients with AA.…”
Section: Received 1 December 2006; Accepted 23 April 2007mentioning
confidence: 99%